The technical landscape for patient-centered CDS: progress, gaps, and challenges. (9th March 2022) - Dullabh, Prashila; Heaney-Huls, Krysta; Lobach, David F; Hovey, Lauren S; Sandberg, Shana F; Desai, Priyanka J; Lomotan, Edwin; Swiger, James; Harrison, Michael I; Dymek, Chris; Sittig, Dean F; Boxwala, Aziz
Abstract: Supporting healthcare decision-making that is patient-centered and evidence-based requires investments in the development of tools and techniques for dissemination of patient-centered outcomes research findings via methods such as clinical decision support (CDS). This article explores the technical landscape for patient-centered CDS (PC CDS) and the gaps in making PC CDS more shareable, standards-based, and publicly available, with the goal of improving patient care and clinical outcomes. This landscape assessment used: (1) a technical expert panel; (2) a literature review; and (3) interviews with 18 CDS stakeholders. We identified 7 salient technical considerations that span 5 phases of PC CDS development. While progress has been made in the technical landscape, the field must advance standards for translating clinical guidelines into PC CDS, the standardization of CDS insertion points into the clinical workflow, and processes to capture, standardize, and integrate patient-generated health data.